Evolutionary history and spatiotemporal dynamic of GIII norovirus: From emergence to classification in four genotypes. Issue 4 (4th June 2021) - Castells, Matías; Cristina, Juan; Colina, Rodney
Abstract: Noroviruses belong to a genetically diverse group of viruses infecting a wide range of mammalian host species, and those detected in cattle and sheep are classified within genogroup III (GIII). The current classification of norovirus in genogroups and genotypes is based on phylogenetic clustering and average distances within and between these phylogenetic clusters; however, the classification studies have been focused mainly on human norovirus, being GIII norovirus relegated. Due to the increasing number of studies on GIII norovirus, the need of an updated and extensive classification is evident. The aim of this study was to update the classification of norovirus within GIII, to describe the emergence of a circulating recombinant strain, and to reconstruct the evolutionary history of this genogroup. Two P‐types (GIII.P1–2) and four genotypes (GIII.1–4) were described. For the genogroup GIII, the evolutionary rate estimated was 2.78E‐3 s/s/y (95%HPD, 1.79E‐3 s/s/y–3.78E‐3 s/s/y), and the tMRCA was estimated around 1500 (95%HPD, 1247–1688). Despite the long history of this genogroup, the genotypes detected at present emerged in the last 100 years. Interestingly, most of the recombinant GIII.2P[1] strains detected worldwide were originated from a single recombination event and this recombinant strain was later dispersed through the world. Finally, our results indicate that a scenario of genotypes replacement through the time is highly probable.